Adverse Reactions of Metrizamide Myelography - Nakamura, S.; Oka, S.; Senzoku, F.; Matsuoka, A.; Saiki, K.; Kawai, S.; Hattori, S.; Kotani, H. (Orthopedics & Traumatology, 1983)
A series of 155 cases, who received various amounts of metrizamide for the purpose of cervical, thoracic and lumber myelography and metrizamide CT scan, has been studied. 79 cases (51%) were found to have various adverse reactions. The adverse reactions were seen in 66.7% of thoracic, 53.8% of cervical, 42.9% of lumbar myelography and in 26.7% of metrizamide CT. Most remarkable complications were mental disorders, which were seen in five cases of cervical myelography. We also found increased paralysis in thoracic myelography and urinary dysfunction in lumbar myelography. The rate of adverse reactions was less by C1-C2 lateral puncture than by lumbar puncture. It is suggested from our series that the maximum dose of total iodine is 2160mgI/ml in cervical, 2700mgI/ml in thoracic and 2250mgI/ml in lumbar myelography.